Development of 18 microsatellite markers for Salvia pratensis. (22nd January 2020) - Krak, Karol; Vít, Petr; Douda, Jan; Mandák, Bohumil
Abstract : Premise: Microsatellite markers were developed for the perennial herb Salvia pratensis (Lamiaceae), a species representative of European dry grasslands. The development of microsatellite markers is needed for genetic and phylogeographical studies of species from the genus Salvia . Methods and Results: We used low‐coverage Illumina sequencing to identify microsatellite loci. Based on these data, we have developed 18 polymorphic microsatellite markers with the number of alleles per locus ranging from two to 15. The levels of observed and expected heterozygosity ranged from 0.05 to 0.95 and from 0.05 to 0.89, respectively. The majority of the markers successfully cross‐amplified in other Salvia species. Conclusions: The markers were shown to be suitable for population genetic and phylogeographic studies in S. pratensis as well as in related species ( S. aethiopis, S. austriaca, S. glutinosa, S. nemorosa, S. nutans, and S. verticillata ) and will be used in the broader context to trace the origins of European dry grasslands.